Membangun Kesadaran Halal: Strategi Door to Door dalam Sosialisasi dan Pendampingan Sertifikasi Halal di Desa Grogol Kediri - Wagini, Nur Laili; Fawaid, M. Bahrul; Cantika S, Adinna; Puja W, Karina; Fadhila A, Nila; Bahrul U, Wildan; Mufida, Irfan; Mustika S, Haeny; Ayu A, Putri; Yulia P, Puput; Mawadah N, Mardiana; Nur A, Arina; Rohmawati, Dwi Nur; Kamila N, Nasyarima; Safitri, Mayang; Zaman, Qomarus (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This service aims to increase awareness of the importance of halal certification among MSMEs in Grogol Village, Kediri, as well as provide assistance in applying for NIB and halal certification. The activity method is carried out through a door-to-door approach, where the KKN team visits MSMEs directly to provide outreach and assistance in the registration process. As a result, six MSMEs succeeded in obtaining NIB, while seven other MSMEs are currently in the halal certification process. This includes four fried onion MSMEs and three upil cracker MSMEs. It is hoped that this activity can help Grogol Village MSMEs improve the quality of their products, develop their businesses at national and international levels, and open up wider employment opportunities. The door-to-door strategy has proven effective in conveying information and providing direct assistance to MSMEs, thereby increasing awareness of the importance of halal certification for their products.